2001
DOI: 10.3917/spub.014.0359
|View full text |Cite
|
Sign up to set email alerts
|

Épidémiologie de l'insuffisance pondérale à la naissance dans le Sahel tunisien

Abstract: Our study aims to assess the determinants and the frequency of low birth weight (LBW) in the health district of Monastir (Tunisia). The study was carried out over a three-year period, beginning in January 1995 and ending in December 1997. According to the Monastir district's childbirth register, 1,194 of the 21,393 newborns delivered were babies born with a low birth weight (LBW rate of 5.6%). Common characteristics among the LBW infants were the following: females are more often affected than males (sex ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
9
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 2 publications
8
9
1
4
Order By: Relevance
“…Il existe donc une association statistiquement significative (p=0,000) entre l’âge maternel (moins de 18 ans et plus de 35 ans) et l’accouchement d’un nouveau-né de petit poids de naissance. Ces résultats cheminent ensemble avec ceux de plusieurs autres auteurs [12–14]. …”
Section: Discussionunclassified
See 3 more Smart Citations
“…Il existe donc une association statistiquement significative (p=0,000) entre l’âge maternel (moins de 18 ans et plus de 35 ans) et l’accouchement d’un nouveau-né de petit poids de naissance. Ces résultats cheminent ensemble avec ceux de plusieurs autres auteurs [12–14]. …”
Section: Discussionunclassified
“…Après 37 semaines, seuls 10,4% des nouveau-nés sont concernés. Nos résultats sont comparables à ceux de la littérature [12, 20]. A ce propos, notons que le faible poids à la naissance résulte soit d’une naissance prématurée (accouchement avant la 37ème semaine d’aménorrhée), soit d’un retard de croissance fœtale des enfants nés à terme [21, 22].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…In Senegal, Faye et al [32] reported extra-uterine growth retardation (86%), underweight (61%), and underweight at 40 weeks post-conception (41%), at 3 months and at 6 months of gestation-adjusted age. Other higher rates of underweight were reported in Morocco (77.5%) [33], Tunisia (55%) [34], China (56.8%) [35] and Japan (49%) [36].…”
Section: Discussionmentioning
confidence: 80%